REKONSTRUKSI SISTEM PEMILIHAN GUBERNUR DAN PEMILIHAN BUPATI/ WALIKOTA DI INDONESIA - Kristiyanto, Eko Noer (Pusat Penelitian Politik, 2015)
Â Local elections are meant to elect the provincial governors and regents/mayors in the district/city. Filling the post of the head of the region at the provincial level is the same as charging regional head office in the city district, which is elected directly by the people. In Indonesia, the enforcement of government embraces the principles of decentralization, deconcentration, and assistance mandate. Deconcentration and assistance mandate are conducted since not all authorities and administration tasks can be performed by using the principle of decentralization. Decentralization is simply defined as delegation of authority. While deconcentration is the delegation of authority from central government to governor as governmentâ€™s representative in the province. Given the differences in the position of the provincial and district/city as well as the difference between the role of governors and regents/mayors, must the implementatiom of local elections be the same among regions?. This paper explains that the elections in the province should be indirect, on the other hand, direct elections must be maintained at the district/city level. There will be many positive things if these two mechanisms are implemented. These mechanisms also do not contradict to the constitution.Keywords: local government, district head, deconcentration, decentralization.Â